The evolutionary origin of the Runx/CBFbeta transcription factors – Studies of the most basal metazoans - Groner Yoram; Levanon Ditsa; Marlow Heather; Reitzel Adam M; Shigesada Katsuya; Eisenstein Miriam; Sher Daniel; Sullivan James C; Finnerty John R; Gat Uri (BMC Evolutionary Biology, 2008)
Abstract Background Members of the Runx family of transcriptional regulators, which bind DNA as heterodimers with CBFβ, are known to play critical roles in embryonic development in many triploblastic animals such as mammals and insects. They are known to regulate basic developmental processes such as cell fate determination and cellular potency in multiple stem-cell types, including the sensory nerve cell progenitors of ganglia in mammals. Results In this study, we detect and characterize the hitherto unexplored Runx/CBFβ genes of cnidarians and sponges, two basal animal lineages that are well known for their extensive regenerative capacity. Comparative structural modeling indicates that the Runx-CBFβ-DNA complex from most cnidarians and sponges is highly similar to that found in humans, with changes in the residues involved in Runx-CBFβ dimerization in either of the proteins mirrored by compensatory changes in the binding partner. In situ hybridization studies reveal that Nematostella Runx and CBFβ are expressed predominantly in small isolated foci at the base of the ectoderm of the tentacles in adult animals, possibly representing neurons or their progenitors. Conclusion These results reveal that Runx and CBFβ likely functioned together to regulate transcription in the common ancestor of all metazoans, and the structure of the Runx-CBFβ-DNA complex has remained extremely conserved since the human-sponge divergence. The expression data suggest a hypothesis that these genes may have played a role in nerve cell differentiation or maintenance in the common ancestor of cnidarians and bilaterians.